Clinical characteristics and outcomes of Castleman disease: A multicenter study of 185 Chinese patients - Xuanye Zhang; Hui‐Lan Rao; Xiaolu Xu; Zhi‐Hua Li; Bing Liao; Hongmei Wu; Mei Li; Xiuzhen Tong; Juan Li; Qingqing Cai (2017)
Castleman disease ( CD ) is a rare lymphoproliferative disorder. To assess the clinical features, outcomes, and prognostic factors of this disease, we retrospectively analyzed 185 HIV ‐negative CD patients from four medical centers in southern China. The median age was 37 years. One hundred and twenty‐one patients (65.4%) were classified as unicentric CD ( UCD ) and 64 patients (34.6%) were classified as multicentric CD ( MCD ). The histology subtype was hyaline‐vascular for 132 patients (71.4%), plasma cell for 50 patients (27%), and mixed type for 3 patients (1.6%). The 5‐year overall survival ( OS ) of 185 CD cases was 80.3%. All UCD patients underwent surgical excision, whereas the treatment strategies of MCD patients were heterogeneous. The outcome for UCD patients was better than MCD patients, with 5‐year OS rates of 93.6% and 51.2%, respectively. In further analysis of the MCD subgroup, a multivariate analysis using a Cox regression model revealed that age, splenomegaly and pretreatment serum albumin level were independent prognostic factors for OS . This multicenter study comprising the largest sample size to date suggested that MCD is a distinct entity from UCD with a significantly worse outcome. Older age (≥40 years), splenomegaly, and hypoalbuminemia were risk factors for poorer MCD prognosis.